Design and analytical validation of a duplex PCR for Ehrlichia and Rickettsia detection in ticks (2017)
ABSTRACT: Ehrlichia and Rickettsia are two major rickettsial genera transmitted by ticks that affect a number of wild and domestic animal species and human populations around the world. Objective: To design and validate a duplex PCR for Ehrlichia and Rickettsia in ticks. Methods:Assay validation included testing for sensitivity,specificity, reproducibility, and robustness of the PCR. The groELand 23sr RNAgenes were used for Ehrlichia and Rickettsia, respectively. Results: The limit of detection was one hundred gene copies per 50 μLof reaction for Ehrlichia spp, and one gene copy of Rickettsia per 50 μL of reaction. In general, the primers of the test only amplified in silico those bacterial agents for which they were originally designed, with the exception of the primers for Rickettsia that also amplified Methylocystis sp. The test was reproducible (intermediate precision) 96.7% of the times for both agents. The test was robust enough to tolerate concentration changes of all reagents with the exception of Taq DNA polymerase. Conclusions: The validation results indicated that this PCR is useful for detection in both bacterial genera and it is a good candidate for diagnostic validation.RESUMEN: Ehrlichia spp. y Rickettsia spp.son dos de los principales géneros rickettsiales transmitidos por garrapatas que afectan a animales silvestres, domésticos y humanos alrededor del mundo. Objetivo: diseñar y validar una prueba PCR duplex para Ehrlichia y Rickettsia en garrapatas. Métodos: la validación de la prueba incluyó ensayos de sensibilidad, especificidad, reproducibilidad y robustez. En la PCR se usó groEL y ARNr 23S como genes blanco para Ehrlichia y Rickettsia, respectivamente. Resultados: el límite de detección fue de 100 copias del gen por 50 μL de reacción para Ehrlichia spp y una copia del gen de Rickettsia por 50 μLde reacción. En general, los cebadores de la prueba solo amplificaron in silico los agentes bacterianos para los cuales fueron originalmente diseñados, con la excepción de los cebadores de Rickettsia que también amplificaron Methylocystis sp. La prueba fue reproducible (precisión intermedia) en un 96.7% de las veces para ambos agentes. La prueba fue suficientemente robusta como para tolerar cambios de concentración de los diferentes reactivos, con excepción de la Taq DNA polimerasa. Conclusión: los resultados de validación indican que la PCR es útil para detectar ambos géneros bacterianos y podría usarse para validación diagnóstica.